Digital Literacy Education: Strategies to Mitigate the Negative Impact of Gadget Addiction on Children in Sukamelang Village - Hilwa Nurul Azkiya (Aimmah: Social Sciences Journal, 2025)
Rapid advances in information technology have transformed the interaction patterns and lifestyles of children in rural areas, where gadget use has become an integral part of their daily lives. However, uncontrolled use triggers the risk of addiction, which negatively impacts physical and psychological health. This article aims to describe the implementation of an educational program that socialized the dangers of gadget addiction among students at SDN 3 Sukamelang. The method used was a participatory approach through interactive lectures, visual demonstrations, and group discussions. The results showed an increase in students' critical awareness regarding time limits on technology use and the impact of radiation, as well as a decrease in social empathy. This program successfully provided a foundation for digital literacy for children and the school to create a healthy learning environment in the digital age.